Formation of students’ readiness for leadership of pupils’ artistic-and-creative activities at the fine arts lessons (Educational Dimension, 2021)
The study reveals the content and essence of students’ artistic-and-creative activity in classes of fine arts. It has been found such activities are a process of creating new, original artistic images, and, at the same time, it is activities for the perception and experience of artistic phenomena through their aesthetic evaluation. Characteristic features of such activity are following: 1) positive motivation, artistic orientation, bright interest, emotional uplift, 2) purposefulness of emotional and figurative kind, special artistic-and-creative disposition; 3) realizing ideas about the subject and analysis of the depicted things that based on visual images; 4) mastering the results of demonstration by the teacher of technical methods, formation of ideas about the image; 5) the presence of an appeared image arising at the beginning of the work, hereafter it is correcting and clarifying during the process of its material embodiment; 6) adequate self-assessment of the result. It has been shown the formation of such experience is dynamic phenomena and can be characterized by means of three stages. The stage 1 is mastering the holistic picture of the world, the experience of artistic practice by students. The next stage 2 is gaining individual experience of artistic creativity, development of guidelines for aesthetic perception of artistic phenomena and objects. Yet another stage 3 is the use and expansion of students’ own artistic experience, the formation their artistic-graphic competences. It has been determined the leadership of pupils’ artistic-and-creative activities by the artist-teacher puts into via pedagogical planning, organizational support, adjustment, analysis and evaluation of results. It has been seen the readiness for leadership of the students’ artistic-and-creative activities at fine arts lessons is a complex integrated personal quality which can be differentiated into motivational, gnostic and praxiological components. It has been substantiated the formation of these components should be a natural process of professional development of future fine arts teachers. The formation of readiness for leadership of the students’ artistic-and-creative activities in future teachers of fine arts is arranged by means of the creation of certain pedagogical terms in the educational process. Among them: ensuring the integrative systemic variety of professional preparation of future teachers of fine arts, the unity of psychological and pedagogical, and special artistic training; development of professional competencies of a teacher of fine arts, pedagogical and artistic mastery; implementation of a step-by-step process of shaping students’ artistic-and-creative activities.
Keywords: profession preparation of future fine arts teachers; artistic-and-creative activities of students; profession readiness; leadership for students’ study activities